Optimality-based dynamic allocation with nonlinear first-order redundant actuators. (September 2016) - Passenbrunner, Thomas E.; Sassano, Mario; Zaccarian, Luca
Abstract: A scheme is proposed to induce optimal input allocation of dynamically redundant nonlinear actuators with first-order dynamics that satisfies suitable regularity and stability assumptions. The allocation scheme is parametrized by a cost function associated with the most desirable actuator configuration, and guarantees convergence to the desired set point as well as to the minimum of the cost function. The overall scheme is also shown to reduce, in some special cases, to a nonlinear version of a PI type of control action.